PENTINGNYA PENDIDIKAN DALAM MENINGKATKAN KESADARAN SOSIAL - Ahmed Dipa Suparwanto a; Mirna Nur Alia Abdullah; Muhamad Retza Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the extent to which education plays a role in increasing social awareness amidst the dynamics of today's society. Social awareness—which includes the values ​​of empathy, tolerance, and responsibility towards others—is a crucial element in creating a balanced and harmonious social life. Through a planned education system that focuses on societal values, individuals are expected to be able to build sensitivity to the social conditions around them. In its implementation, this study uses a qualitative descriptive method with a literature study approach. Data were obtained through a review of various academic sources such as scientific journals, books, and relevant articles, which discuss the relationship between education and the formation of social awareness. The analysis focuses on understanding the theory of character education, learning models, and educational policies that support the instillation of social values. The findings of this study indicate that education plays an important role in fostering social awareness. Key factors influencing this process include the integration of social values ​​in learning, the role of educators as role models, and contextual learning methods. However, the implementation process still faces obstacles, especially in the education system that tends to prioritize intellectual aspects alone. Therefore, a comprehensive and balanced educational strategy is needed between academic development and social aspects.